Teaching English as a second language using charts - Sasi Bhushan, S. (International Journal of Psychosocial Rehabilitation, 2024)
In the modern days, there are various tools available to teach a Second Language (L2) like English in a better way. One of the tools is visual aids. Visual aids include film, slide, or model. One of the best visual aids that can be used in an L2 classroom is charts. Charts are thick papers of big sizes available in different colors, which attract the attention of everyone. This paper presents the study of charts being used in a classroom to make the learners learn an English quickly and in an enjoyable manner. The participants are 60 first-year engineering learners from an institution in Srikakulam district, Andhra Pradesh, India. At the end of the study, it is found that the students feel easy and glad to learn new things in English easily with the chart-based method.